2014
DOI: 10.1016/j.fgb.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the fumonisin biosynthetic gene cluster in fumonisin-producing and nonproducing black aspergilli

Abstract: The ability to produce fumonisin mycotoxins varies among members of the black aspergilli. Previously, analyses of selected genes in the fumonisin biosynthetic gene (fum) cluster in black aspergilli from California grapes indicated that fumonisin-nonproducing isolates of Aspergillus welwitschiae lack six fum genes, but nonproducing isolates of Aspergillus niger do not. In the current study, analyses of black aspergilli from grapes from the Mediterranean Basin indicate that the genomic context of the fum cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 59 publications
(112 reference statements)
11
62
0
Order By: Relevance
“…On the contrary, the presence of A. welwitschiae strains that produce both OTA and FB2 is worrisome, since both of these mycotoxins are considered by the International Agency for Cancer Research (IARC) group 2b, meaning potentially carcinogenic. Only a minority of strains analyzed were able to produce only OTA, while the majority of A. welwitschiae strains (80%) also produced FB2, in agreement with previous reports [33,35]. Some authors have demonstrated that OTA production in A. niger is affected by temperature [36], while in A. welwitschiae, it is affected by water activity and the medium [37].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the contrary, the presence of A. welwitschiae strains that produce both OTA and FB2 is worrisome, since both of these mycotoxins are considered by the International Agency for Cancer Research (IARC) group 2b, meaning potentially carcinogenic. Only a minority of strains analyzed were able to produce only OTA, while the majority of A. welwitschiae strains (80%) also produced FB2, in agreement with previous reports [33,35]. Some authors have demonstrated that OTA production in A. niger is affected by temperature [36], while in A. welwitschiae, it is affected by water activity and the medium [37].…”
Section: Discussionsupporting
confidence: 89%
“…OTA residue was dissolved with 1 mL of acetonitrile/water/glacial acetic acid (99:99:2, v/v/v) and filtered using RC through a 0.20 µm regenerated cellulose filter and determined by HPLC/FLD. OTA quantification was performed according to Susca et al [35]. The quantification limit (LOQ) was 0.05 µg/g based on a signal to noise ratio of 10:1.…”
Section: Mycotoxin Analysesmentioning
confidence: 99%
“…Based on the current knowledge about the biosynthesis of these mycotoxins, BLAST analyses were performed to check the mycotoxins production potentiality in A. tubingensis G131 strain, a methodology that was already described for different genomic works on Aspergillus sp. [27,43,44].…”
Section: Focus On Putative Mycotoxins Productionmentioning
confidence: 99%
“…The fumonisin gene cluster of A. niger contains at least 14 fum genes [43]. A previous study showed that A. luchuensis NBRC 4314 genome only contains orthologues for fum1 and fum15 with high identity: 68 and 72%, respectively [27].…”
Section: Focus On Putative Mycotoxins Productionmentioning
confidence: 99%
See 1 more Smart Citation